Shooting the messenger criminalising journalism - Fowler, Andrew (The criminalization of political dissent, 2018)
If the Al-Qaeda terrorists who attacked the United States in 2001 wanted to weaken the West, they achieved their mission by striking a blow at the heart of democracy. Since 9/11 governments including those of the USA, the UK, France and Australia have introduced tough, intimidating legislation to discourage the legitimate activities of a probing press, so greatly needed after the Iraq War proved that executive government could not be trusted. Often hiding behind arguments about defending national security and fighting the war on terror, governments criminalised legitimate journalistic work, ramping up their attacks on journalists' sources, and the whistle-blowers who are so essential in keeping governments honest. Through detailed research and analysis, this book, which includes interviews with leading figures in the field, including Edward Snowden, explains how mass surveillance and anti-terror laws are of questionable value in defeating terrorism, but have had a 'chilling effect' on one of the foundations of democracy: revelatory journalism